2011
DOI: 10.1152/ajplung.00062.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces downregulation of PPAR-γ in isolated pulmonary arterial smooth muscle cells and in rat lung via transforming growth factor-β signaling

Abstract: Chronic hypoxia activates transforming growth factor-β (TGF-β) signaling and leads to pulmonary vascular remodeling. Pharmacological activation of peroxisome proliferator-activated receptor-γ (PPAR-γ) has been shown to prevent hypoxia-induced pulmonary hypertension and vascular remodeling in rodent models, suggesting a vasoprotective effect of PPAR-γ under chronic hypoxic stress. This study tested the hypothesis that there is a functional interaction between TGF-β/Smad signaling pathway and PPAR-γ in isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…In the pulmonary vasculature, RG treatment was shown to attenuate pulmonary arterial hypertension and vascular remodeling in chronic-hypoxia mouse models. Mechanisms include alterations in NADPH subunit expression, superoxide levels, regulation of Nox4 expression through NF-kappaB, and a down regulation of PPARγ through transforming growth factor-beta (15)(16)(17). Thus, the findings of the present study are consistent with this emerging literature, but are unique in demonstrating a role for PPARγ in early selective pulmonary vascular endothelial dysfunction secondary to increased pulmonary blood flow.…”
Section: Discussionsupporting
confidence: 86%
“…In the pulmonary vasculature, RG treatment was shown to attenuate pulmonary arterial hypertension and vascular remodeling in chronic-hypoxia mouse models. Mechanisms include alterations in NADPH subunit expression, superoxide levels, regulation of Nox4 expression through NF-kappaB, and a down regulation of PPARγ through transforming growth factor-beta (15)(16)(17). Thus, the findings of the present study are consistent with this emerging literature, but are unique in demonstrating a role for PPARγ in early selective pulmonary vascular endothelial dysfunction secondary to increased pulmonary blood flow.…”
Section: Discussionsupporting
confidence: 86%
“…Administration of GKT137831 or rosiglitazone attenuated hypoxic reductions in lung PPARg expression ( Figure 7A). Transforming growth factor (TGF)-b1 contributes to hypoxiamediated Nox4 expression and activity and HPASMC proliferation (24,(28)(29)(30), and PPARg ligands have been shown to modulate TGF-b1 signaling in the lung (31)(32)(33). We therefore examined the impact of Nox4 inhibition with GKT137831 on hypoxia-induced TGF-b1 expression in the lung.…”
Section: Administration Of Gkt137831 or Rosiglitazone Attenuates Hypomentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor (PPAR) g belongs to a kind of ligand-activated nuclear hormone receptor superfamily, which is ubiquitously expressed in pulmonary vascular endothelial and smooth muscle cells, and acts as a transcription factor to modulate the transcription of a number of genes (8). Previous studies reported that PPARg is down-regulated in the lungs (9,10) and distal PAs (11) of experimental PH models, whereas restoration of PPARg by specific agonists can markedly attenuate the PH pathogenesis by normalizing the elevated right ventricle systolic pressure and distal PA remodeling (12)(13)(14). Moreover, we further demonstrated the molecular mechanisms that PPARg inhibits PA remodeling and PASMC proliferation, mainly by targeting SOCE and TRPC proteins (11,13).…”
mentioning
confidence: 99%